Stages in evolution of Earth's crust recorded by the Huliaipole block of the West Azov area (4.0-2.0 Ga) - Artemenko, G.V.; Shumlyanskyy, L.V.; Wilde, S.A.; Whitehouse, M.J.; Bekker, A.Yu. (Доповіді НАН України, 2020)
The U-Pb age of zircon populations from metadacite of the Huliaipole Suite was determined using the LA-ICP-MS method as 3085-2850 and 3700-3360 Ma. In addition, two crystals of zircon were discovered with an age of more than 3800 Ma. According to geological and geochronological data, the Huliaipole Block, 30 × 50 km in size, is composed of rocks and relicts of the Hadean, Archean, and Palaeoproterozoic eons. The oldest nucleus of the Azov Domain was probably formed from 3.97 to 3.3 Ga ago. In the Mesoarchean (3.2-3.0 Ga), it became a part of the Middle Dnieper-Azov-Kursk granite-greenstone terrane. Felsic and intermediate volcanics of the Huliaipole Suite could have formed due to the melting of the sialic crust, including rocks of the Hadean and Archean age, as a result of the underplating of basic melts during the formation of the Neoarchean to Paleoproterozoic rift structures.